A conceptual model of alcohol use and adherence to antiretroviral therapy: systematic review and theoretical implications for mechanisms of action. Issue 1 (2nd January 2022) - Woolf-King, Sarah E.; Sheinfil, Alan Z.; Ramos, Jeremy; Foley, Jacklyn D.; Moskal, Dezarie; Firkey, Madison; Kellen, David; Maisto, Stephen A.
ABSTRACT: Alcohol consumption is one of the most prevalent correlates of antiretroviral therapy (ART) adherence, yet causal processes underlying this association remain largely unexplored. The goal of this systematic review was to develop a conceptual model that describes the causal effect of alcohol consumption on ART nonadherence. We reviewed 230 studies that examined the association between alcohol consumption and ART adherence with three primary aims: (1) to replicate and extend previous reviews of the literature, (2) to summarize and critique study designs capable of answering questions about temporal overlap and (3) to summarize potential mechanisms of action. A model of alcohol-associated ART nonadherence was proposed to guide future work, integrating general theories of ART adherence and theory on the psychological and behavioral effects of alcohol intoxication. The conceptual model describes two mechanistic processes—prospective memory impairment and interactive toxicity beliefs/avoidance behaviors—involved in alcohol-associated intentional and unintentional nonadherence, respectively. This model can be used to guide future research on the causal processes involved in the frequently observed correlation between alcohol consumption and adherence.